The Bioethicist as Healer - Dubois, James M. (The Hastings Center report, 2024)
Combativeness is a social illness. We are surrounded by culture wars over abortion, vaccine mandates, transgender care, how we die, and even how we define death. The problem is not that we disagree, but how we disagree: too often, with anger, aggression, and a sense of urgency to win against the other. Bioethicists have the knowledge and skills needed to model constructive disagreement and respectful calls for change. Bioethicists may have increased awareness that everyone suffers from unconscious self-serving biases—we are all imperfect. They are trained to recognize competing values and to engage in processes of balancing values in social contexts. Clinical ethicists are additionally trained in mediation, which involves acknowledging goodwill, listening deeply, apologizing when needed, and seeking common ground. In short, bioethicists have many of the tools needed to be healers of a culture afflicted with combativeness.